An Assessment of Hand-Held XRF Analyser Performance for the Characterisation of Aluminium Scrap - Angeliki Ntourntoureka; Michail Galetakis; Vasileios Deligiorgis (Materials Proceedings, 2023)
The characterisation of aluminium scrap plays a crucial role in its recycling, and hand-held X-ray fluorescence (XRF) analysers offer a portable and efficient solution for on-site analysis. This study focuses on assessing the performance of a hand-held XRF analyser for the characterisation of aluminium scrap using the gage repeatability and reproducibility (Gage R&R) method.